2008
DOI: 10.1179/136485908x252287
|View full text |Cite
|
Sign up to set email alerts
|

Febrile status, malarial parasitaemia and gastro-intestinal helminthiases in schoolchildren resident at different altitudes, in south–western Cameroon

Abstract: In the many areas where human malaria and helminthiases are co-endemic, schoolchildren often harbour the heaviest infections and suffer much of the associated morbidity, especially when co-infected. In one such area, the Buea district, in south-western Cameroon, two cross-sectional surveys, together covering 263 apparently healthy schoolchildren aged 4-12 years, were recently conducted. The prevalences of fever, malarial parasitaemia and intestinal helminth infections, the seroprevalences of anti-Plasmodium fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
63
3

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(75 citation statements)
references
References 63 publications
9
63
3
Order By: Relevance
“…STH in this case) in children has been associated with their particularly poor hygiene (at home) and recreational or other activities that regularly bring them close to areas contaminated with human feces. 15,33 Based on available data, we found the positive association between malaria and hookworm was pronounced in pregnant mothers; a stream of bioimmunological mechanisms appeared to be involved in such interactions. Not all of these interactions are mutually exclusive and some are worthy of special mention.…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…STH in this case) in children has been associated with their particularly poor hygiene (at home) and recreational or other activities that regularly bring them close to areas contaminated with human feces. 15,33 Based on available data, we found the positive association between malaria and hookworm was pronounced in pregnant mothers; a stream of bioimmunological mechanisms appeared to be involved in such interactions. Not all of these interactions are mutually exclusive and some are worthy of special mention.…”
Section: Discussionmentioning
confidence: 92%
“…Among school-aged children, the pooled analysis of three studies (n¼476) 32,33,49 showed that there was comparable mean Hb levels in the two groups (MD: 0.47; 95% CI:20.1 to 1.03). The pooled estimates of two studies 43,51 gave a higher risk of anemia in those co-infected with A. lumbricoides (summary OR: 2.72; 95% CI: 1.11-6.7; I 2 : 0%).…”
Section: Effect Of Co-infection On Anemiamentioning
confidence: 99%
See 1 more Smart Citation
“…School-aged children have been reported to be at the highest risk of co-infections of both malaria and STHs and consequently anaemia [12,13]. Although a number of studies have been carried out on malaria and STHs coinfections [13][14][15] in the Mount Cameroon region, none has specifically focused on the influence of urbanization on coinfections in school children. This study was therefore aimed at finding out if the level of urbanization influences the prevalence and intensity of co-infections of malaria and STHs in school children in the Mount Cameroon Region.…”
Section: Introductionmentioning
confidence: 99%
“…Infections by intestinal helminths have been shown to result in abdominal pain, diarrhea, anaemia, malnutrition, ulcers, intellectual retardation, cognitive and educational deficits, intestinal obstruction and, in severe chronic and untreated infections, could even lead to death (Crampton and Nesheim, 2002;Hotez et al, 2008;Hall et al, 2008;Brooker et al, 2010). In the context of continuous exposure to Anopheles mosquitoes, these conditions are further exacerbated with asymptomatic malaria parasites, often resulting in co-infections with Plasmodium, and thus, putting these children at enhanced risk of clinical disease (Mwangi et al, 2006;Nkuo-Akenji et al, 2006;Achidi et al, 2008).…”
Section: Introductionmentioning
confidence: 99%